2013
DOI: 10.1021/ja4007244
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Organocatalytic Thio-Diels–Alder Reactions via Trienamine Catalysis

Abstract: We report a new process to access highly enantioenriched sulfur-based heterocycles by an asymmetric catalytic thio-Diels-Alder reaction. Thiocarbonyls are challenging heterodienophiles in enantioselective Diels-Alder reactions, due to their inherent high reactivity and their poor ability to coordinate to chiral catalysts. We successfully circumvented these problems by employing a different strategy, which explores the use of in situ generated catalyst-bound dienes. Synthetically useful dihydrothiopyrans as wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(29 citation statements)
references
References 74 publications
0
26
0
3
Order By: Relevance
“…[53] Theuse of adienophile with an ucleophilic site enabled a[ 4 + +2] cycloaddition with trienamines followed by ring closure,d emonstrating an e,b,ipsoreactivity pattern. Thea pplication of 2,4-dienals and cyanoacrylamides illustrated the high levels of molecular complexity that can be obtained with trienamine chemistry.T he bicyclicmolecules enabled the formation of five stereocenters and bicyclic structures in ao ne-pot reaction affording the products in 70-98 % ee.R ecently,h etero-Diels-Alder reactions of trienamines were also reported, [54] enabling the synthesis of optically active heterocycles containing either sulfur or nitrogen (Scheme 5).…”
Section: Trienamine Catalysismentioning
confidence: 99%
“…[53] Theuse of adienophile with an ucleophilic site enabled a[ 4 + +2] cycloaddition with trienamines followed by ring closure,d emonstrating an e,b,ipsoreactivity pattern. Thea pplication of 2,4-dienals and cyanoacrylamides illustrated the high levels of molecular complexity that can be obtained with trienamine chemistry.T he bicyclicmolecules enabled the formation of five stereocenters and bicyclic structures in ao ne-pot reaction affording the products in 70-98 % ee.R ecently,h etero-Diels-Alder reactions of trienamines were also reported, [54] enabling the synthesis of optically active heterocycles containing either sulfur or nitrogen (Scheme 5).…”
Section: Trienamine Catalysismentioning
confidence: 99%
“…As an example, as many as four new stereocenters can be prepared in a single step using the DA reaction (Scheme ). There are an enormous number of reports in which the DA reaction was applied for the synthesis of new materials and natural products . Quite recently, cyclopentadienes with Raman and electrochemically active tags were patterned covalently onto graphene surfaces using force‐accelerated DA reactions …”
Section: Introductionmentioning
confidence: 99%
“…15 In a recent study, the volume parameters of the reaction of thiobenzophenone with isoprene were determined, and on this basis the authors concluded that a concerted reaction mechanism is followed. 16 In recent reports, asymmetric thia-Diels-Alder reactions of activated dithioesters 17 as well as of aryl-and hetaryl thioketones 18 with an in-situ-generated chiral trienamine were presented. In the second case, a stepwise reaction mechanism via diradical intermediates was proposed.…”
mentioning
confidence: 99%